An overview of security and privacy in smart cities' IoT communications - Al‐Turjman, Fadi; Zahmatkesh, Hadi; Shahroze, Ramiz (Transactions on emerging telecommunications technologies, 2022)
Smart cities have brought significant improvements in quality of life and services to citizens and urban environments. They are fully enabled to control the physical objects in real time and provide intelligent information to citizens in terms of transport, healthcare, smart buildings, public safety, smart parking, and traffic system and smart agriculture, and so on. The applications of smart cities are able to collect sensitive information. However, various security and privacy issues may arise at different levels of the architecture. Therefore, it is important to be aware of these security and privacy issues while designing and implementing the applications. This paper highlights main applications of smart cities and addresses the major privacy and security issues in the architecture of the smart cities' applications. It also reviews some of the current solutions regarding the security and privacy of information‐centric smart cities' applications and presents future research challenges that still need to be considered for performance improvement. This paper highlights main applications of smart cities and addresses the major privacy and security issues in the architecture of the smart cities' applications. This paper also reviews some current solutions regarding the security and privacy of smart cities' applications and presents future research challenges that still need to be considered for performance improvement.